2011
DOI: 10.1038/ni.2049
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing clusters of the adaptor Lat do not participate in early T cell signaling events

Abstract: Engaged T cell antigen receptors (TCRs) initiate signaling through the adaptor protein Lat. In quiescent T cells, Lat is segregated into clusters on the cell surface, which raises the question of how TCR triggering initiates signaling. Using super-resolution fluorescence microscopy, we found that pre-existing Lat domains were neither phosphorylated nor laterally transported to TCR activation sites, which suggested that these clusters do not participate in TCR signaling. Instead, TCR activation resulted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
328
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 305 publications
(348 citation statements)
references
References 50 publications
9
328
2
Order By: Relevance
“…Each localisation is then disturbed by Gaussian noise with variance drawn from a Gamma distribution with mean 30 nm and standard deviation 13 nm (emulating the localisation error of the microscope). These parameters were chosen to approximately reflect typical clustering behaviour of proteins at the immunological synapse 14,15,20,21 . The three remaining scenarios have the same parameters as the Standard Conditions except where stated otherwise.…”
Section: Performance and Sensitivity Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Each localisation is then disturbed by Gaussian noise with variance drawn from a Gamma distribution with mean 30 nm and standard deviation 13 nm (emulating the localisation error of the microscope). These parameters were chosen to approximately reflect typical clustering behaviour of proteins at the immunological synapse 14,15,20,21 . The three remaining scenarios have the same parameters as the Standard Conditions except where stated otherwise.…”
Section: Performance and Sensitivity Analysismentioning
confidence: 99%
“…To investigate and quantify clustering behaviour, widely used are Ripley's K-function [14][15][16] and pair-correlation (PC) analysis 17,18 . Both rely on drawing a series of concentric shapes -circles in the case of the K-function and tori in the case of PC -around each localisation and counting the number of neighbours enclosed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This way the authors showed that TCR signalling depends on Lat molecules that are associated with intracellular vesicles, rather than pre-existing clusters of Lat molecules at the plasma membrane. These observations helped determine that it is vesicular Lat and not plasmamembrane-bound Lat which makes the bulk contribution to signalling [197].…”
Section: Signalling Dynamic Assembly Of Proteinsmentioning
confidence: 97%